2006
DOI: 10.1038/sj.jcbfm.9600382
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Wound Healing after Cerebral Hypoxia—Ischemia in the Diabetic Mouse

Abstract: Impaired peripheral wound healing is a hallmark of diabetis pathology and has been attributed to compromised macrophage activation. Stroke is another component of diabetic pathology, with increased tissue infarction and worsened recovery although the mechanisms remain unresolved. In this study, we investigated whether a compromised glial/macrophage response might contribute to cerebral hypoxic-ischemic (H/I) brain damage in diabetic (db/db), relative to their normoglycemic db/ + mice. Hypoxia-ischemia was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 39 publications
3
57
0
1
Order By: Relevance
“…In vitro LPS stimulation of peritoneal macrophages from diabetic mice attenuated the inflammatory response [187]. The blunted inflammatory response in diabetic macrophages was also reported in db/db mice, with decreased microglial activation and proinflammatory cytokines in the stroked brain [188]. Microglial activation and the release of inflammatory factors are critical steps in eliciting a rapid inflammatory response in the context of injury.…”
Section: Diabetesmentioning
confidence: 80%
See 1 more Smart Citation
“…In vitro LPS stimulation of peritoneal macrophages from diabetic mice attenuated the inflammatory response [187]. The blunted inflammatory response in diabetic macrophages was also reported in db/db mice, with decreased microglial activation and proinflammatory cytokines in the stroked brain [188]. Microglial activation and the release of inflammatory factors are critical steps in eliciting a rapid inflammatory response in the context of injury.…”
Section: Diabetesmentioning
confidence: 80%
“…These conditions are often associated with the exacerbation of ischemic outcomes and are predictive of worse recovery [186]. The inclusion of hyperlipidemia and diabetes in animal models of stroke has demonstrated that these conditions modulate postischemic inflammatory responses and lesion development [101,152,187,188]. In addition, increased inflammatory factors such as cytokines, chemokines, and adhesion molecules in peripheral monocytes/macrophages in these conditions suggest that peripheral immune status modulates CNS injury.…”
Section: Modulatory Function Of Mononuclear Phagocytes In Comorbiditiesmentioning
confidence: 99%
“…Both type I and type II diabetic patients are two to six times more likely to experience a stroke than nondiabetic patients (Bonow and Gheorghiade, 2004); both morbidity and mortality after stroke are greatly enhanced, although the underlying mechanisms are still unknown. Initially, it was considered that preischemic hyperglycemia and consequent cerebral lactoacidosis were the primary cause (Folbergrova et al, 1992), however, we and others have indicated that additional factors have a significant role in the compromised recovery (Kumari et al, 2007;Nedergaard, 1987;Nedergaard and Diemer, 1987;Vannucci et al, 2001b;Zhang et al, 2004). Recently, we proposed that there is impairment in the acute inflammatory response in the diabetic db/db mouse after a unilateral cerebral hypoxic-ischemic (H/I) insult (Kumari et al, 2007;Zhang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Blood glucose was measured on alternate days during treatment. After 1 week of treatment, cerebral hypoxia-ischemia was induced as reported earlier (Kumari et al, 2007;Vannucci et al, 2001a). Briefly, the right carotid artery was exposed and permanently ligated.…”
Section: Animal Proceduresmentioning
confidence: 99%
See 1 more Smart Citation